Comparative study between isolated and sequential by-pass - Filgueira, José Luis; Cassinelli, Mauricio; Estable, Héctor; Lorenzo, Alberto; Scola, Ricardo (Cirugía del Uruguay, 1983)
Two series of 105 consecutive patients submitted to myocardial revascularisation surgery are reported.